1984
DOI: 10.1002/aja.1001710205
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cultured atrial cardiac muscle cells from adult rats

Abstract: Atrial cardiac muscle cells enzymatically isolated from adult rats were maintained in culture for 0-17 days and examined by transmission electron microscopy (TEM). Cells were stained with conventional TEM stains as well as with osmium ferrocyanide and tannic acid. Our results show that cultured adult atrial cells are capable of in vitro ultrastructural reorganization and possess differentiated ultrastructural characteristics including specific atrial granules, sarcomerically arranged myofilaments, appropriatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…1f ). At all passages studied (10,20,34, and 86), HL-1 cells possessed perinuclear ANF-containing specific granules (Fig. 1 c, g, and h), cardiac-specific myosin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1f ). At all passages studied (10,20,34, and 86), HL-1 cells possessed perinuclear ANF-containing specific granules (Fig. 1 c, g, and h), cardiac-specific myosin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These cardiac characteristics of HL-1 cells include the following: (i) an ultrastructure similar to primary cultures of adult atrial cardiac myocytes (20) and AT-1 cells (3); (ii) cytoplasmic reorganization and myofibrillogenesis similar to that observed in mitotic cardiomyocytes of the developing heart (17); (iii) presence of highly ordered myofibrils and cardiac-specific junctions in the form of intercalated discs (Fig. 1); (iv) the ability to undergo spontaneous contractions while remaining in a mitotic state typical of normal in vivo immature mitotic cardiomyocytes; (v) expression of ANF, ␣-MHC, ␣-cardiac actin, desmin, and connexin43; and (vi) presence of several voltage-dependent currents that are characteristic of a cardiac myocyte phenotype, particularly the I Kr current, which has not been identified in noncardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This association suggested that the thick and thin filaments were being synthesized de novo. A similar sequence of events has been reported as a feature of cultured myocytes from adult rat ventricles (Moses and Claycomb, 1982a,b;Nag et al, 1983) and atria (Cantin et al, 1981;Moses and Claycomb, 1984). Some investigators (Claycomb and Palazzo, 1980;Nag et al, 1983; have suggested that the myocytes undergo a transient structural "dedifferentiation" which is followed by a "redifferentiation."…”
Section: Discussionmentioning
confidence: 68%
“…Where photomicrographs were in cluded, the recovered atrial cell suspensions were found to contain both rounded (50-95%) and rod-shaped myocytes [16]. Moses and Claycomb [ 18] used a simple collagenase dissociation protocol which resulted in a sus pension of 'slender and cylindrical' atrial myocytes; however, within a 24-hour period these myocytes also became spherical in ap pearance. The rounded cells observed in each of these studies appear to be identical to the cells identified in our preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have recently de scribed dissociation methods for adult, mam malian atrial tissue [16][17][18]21]. In two re ports, collagenase was used in combination with a nonspecific protease or hyaluronidase [16,17].…”
Section: Discussionmentioning
confidence: 99%